Hard tissue formation in odontogenic lesions associated with impacted tooth: Plausible pathogenesis - Arush Thakur; Pooja Siwach; Ruchika R Agrawal (Wolters Kluwer Medknow Publications, 2020)
Odontogenesis is a complex process, which involves the molecular interaction between the epithelium and ectomesenchyme called as epithelium mesenchymal interaction (EMI). Reduced enamel epithelium (REE) after tooth formation protects enamel from coming in contact with adjacent ectomesenchyme. Also, REE acts as a source of origin for odontogenic lesions, during the process of development of a lesion, disruption in REE may occur and lead to formed enamel coming in contact with adjacent ectomesenchyme leading to the formation of cementum like calcifications. REE may play a role in pathogenesis of hard tissue formation in odontogenic lesions.